PENGARUH HUKUM BISNIS TERHADAP PENGATURAN PERSAINGAN PERUSAHAAN PRODUK SERUPA - Hutagaol, Ramses; Joy Hutagalung; Frans Tampubolon; Ferdinan J.A Lumban Tobing; Toman Sony Tambunan (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Business activities that are now widely carried out by business actors are not free from competition. This competition sometimes leads to violations of the law in order to achieve maximum profit. They even carry out unfair competition/unfair competition. This unfair business competition will harm the public interest. This competition is now also widespread in business activities in Indonesia and other countries in general. Although before the issuance of Law no. 5 of 1999, the regulation regarding unfair business competition was actually based on Article 1365 of the Civil Code concerning unlawful acts and Article 382 bis of the Criminal Code. There is so much competition between companies producing similar products that it requires business law that can regulate it all so that it runs perfectly without anyone feeling disadvantaged.